(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Two field experiments were conducted concurrently during the 2024 rainy season at Gerki and Salahawa villages of Batagarawa Local Government Area, Katsina State, Nigeria, to determine the influence of three intra-row spacings and three NPK fertilizer application rates on the growth and yield of the finger millet variety. The trial was carried out with three intra row spacing (75 x 15cm, 75 x 20cm and 75 x 25cm) and three different rates of NPK fertilizer application (N30 P15 K15, N60 P30 K30 and N90 P45 K45) the treatments were factorize and laid under randomize complete block deign (RCBD) with three replications. Data on growth and yield-related components were recorded during the experiment. From the result obtained it is confirmed that intra-row spacing of 75 x 25cm significantly (P<0.05) recorded the highest growth and yield values on number of panicle per plant, number of stem per stand, panicle weight per plant, number of stand at harvest and dry matter weight while 75 x 15cm recorded the highest yield per net plot at Salahawa village. Similarly, the three levels of NPK fertilizer application were measured, the result indicated that application of NPK fertilizer at the rate of N90 P45 K45 significantly (P<0.05) performed better than application of fertilizer at N60 P30 K30 and N30 P15 K15 rates in all the growth and yield parameters tested. In conclusion, planting finger millet with an intra-row spacing of 75 x 25cm and applying NPK fertilizer at N90 P45 K45 is recommended in the study area.